Analisa Kebijakan Dinas Lingkungan Hidup dan Keberaihan Terhadap Kesejahteraan Pekerja THL Kebersihan Kabupaten Karawang - Riska Oktavia; L Lukmanul Hakim; Indra Aditya (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the policy of the Department of Environment and Hygiene in providing welfare for workers who are included in the Freelance Daily Workers section or often known as THL. The theory used to analyze this problem using Wilan N Dunn's policy analysis includes information obtained, such as: Policy Problems, Policy Actions and Policy Results. The method used is descriptive qualitative with triangulation data collection techniques which include unstructured interviews, non-participant observations and documentation studies, then the data is analyzed through three stages which include reduction, presentation and conclusion drawing. The results of this study indicate that the quality of the performance of the institutions authorized to make policies, namely the Regional People's Representative Council and the DLHK has been said to be optimal. This can be seen from the performance indicators that have been carried out recently by DLHK which strives for THL Hygiene workers to be given welfare and the quantity of THL Hygiene performance has also been optimal.